Resultados materno perinatales adversos en preeclampsia severa de inicio precoz y tardío. Hospital Regional Docente de Trujillo 2010 - 2014 - Crespín Ramos, Lili Fiorela (2018)
To determine if the adverse maternal perinatal results in severe preeclampsia of early onset are more frequent than in severe preeclampsia of late onset, in Hospital Regional Docente de Trujillo 2010-2014. Material and method: Descriptive, comparative cross-sectional study. Population was conformed by all patients diagnosed with severe preeclampsia who met the inclusion criteria. To compare if there is a significant difference of the results in both groups, the Z-test of difference of proportions was used, considering a level of significance of 5% (p-value <0.05). Results: Adverse maternal results occurred in 17% and 59% of pregnant women with severe preeclampsia of late and early onset, this difference being statistically significant (p-value <0.05). Adverse perinatal results occurred in 38.4% and 82% of pregnant women with severe preeclampsia of late and early onset, this difference being statistically significant (p-value <0.05). Conclusions: Maternal perinatal adverse outcomes in pregnant women with severe preeclampsia of early onset are more frequent than in pregnant women with severe late onset preeclampsia, attended at the Regional Teaching Hospital of Trujillo 2010-2014